Lower limbs muscle activation during instep kick in soccer: effects of dominance and ball condition. Issue 1 (2nd January 2022) - Rabello, Rodrigo; Bertozzi, Filippo; Galli, Manuela; Zago, Matteo; Sforza, Chiarella
ABSTRACT: Muscle activation has been studied in soccer players kicking stationary balls with the dominant foot. This study evaluated swinging and support limb muscle activation during the instep kick using different feet and ball approach conditions.Vastus medialis (VM), biceps femoris (BF), gastrocnemius medialis (GM) and tibialis anterior (TA) activations were evaluated during maximal instep kicks with both feet and the ball in five conditions (n = 18): stationary (STAT), approaching anteriorly (ANT), posteriorly (POST), laterally (LAT) and medially (MED). A repeated-measures two-way ANOVA compared activations between feet and ball conditions throughout the kicking (0–100%) and follow-through phases (101–200%). Close to ball contact (81–124%), non-dominant support GM had greater activation than the dominant one. The LAT and MED conditions differed within the cycle in the swinging VM (0–21%; 191–200%), BF (13–70%; 121–161%), GM (22–82%; 121–143%) and TA (0–32%; 55–97%; 186–200%) and in support VM (0–81%), BF (6–24%; 121–161%) and GM (24–87%). Players require greater support GM activation to stabilize the ankle during non-dominant kicks. Muscle activation differences between LAT and MED indicate that the kicking strategies are altered when kicking balls approaching from different directions.